1980
DOI: 10.1073/pnas.77.1.550
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analyses of murine immunoglobulin heavy chain and serum prealbumin genes establish their location on chromosome 12 proximal to the T (5;12) 31H breakpoint in band 12F1.

Abstract: Analysis of backcross mice carrying the Harwell translocation T(5;12)31H has led to the definitive localization of the immunoglobulin heavy chain gene cluster. BothIgh-1 and Pre-] loci were found to segregate in tight linkage with the chromonomal markers S and 125, which define the balanced translocation T(5^12)31H. Additional data establish the location of these genes at the telbmeric end of chromosome 12. That both lci are proximal to the chromosomal breakpoint in band 12F1 is shown by the phenotypes of segr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…The L chain loci are usually in the embryonic configuration; that is, their gene segments have not been joined to form functional L chain genes (4). The line is diploid for chromosome 12 (3), which carries the H chain locus (5,6). In both homologous chromosomes, the V, D, and J gene segments have been correctly joined to form H chain genes (7).…”
mentioning
confidence: 99%
“…The L chain loci are usually in the embryonic configuration; that is, their gene segments have not been joined to form functional L chain genes (4). The line is diploid for chromosome 12 (3), which carries the H chain locus (5,6). In both homologous chromosomes, the V, D, and J gene segments have been correctly joined to form H chain genes (7).…”
mentioning
confidence: 99%
“…Our data fulfil this prediction and further substantiate the current notion that the chromosome banding similarity reflects the conservation of the homologous gene in different species, as have been shown by comparative gene mapping (Human Gene Mapping 5, 1979;Garver et al 1980). In this context, a recent report of Schroder et al (1980) may merit special attention, who suggested the immunoglobulin heavy chain (Igh) locus of the rat on chromosome 14, in spite of the fact that Igh locus of the mouse have been assigned to chromosome 12 but not to chromosome 17 coding for H-2 complex (Hengartner et al 1978;Meo et al 1980). Wiener et al (1982), however, are of opinion that the rat Igh is located on chromosome 6, which is similar to mouse chromosome 12.…”
Section: Immunoselection Of the Hybrid Clonesmentioning
confidence: 99%
“…The lgh complex is on the murine 12th chromosome and contains the genes (Igh-C) that encode the constant (C) portion of/~, 6, 3', a, and e immunoglobulin (Ig) heavy chains together with J, D, and V region genes that encode their corresponding variable (V) regions (1)(2)(3). In addition to these Igh genes, there are several other linked genes, some of which may play a role in immune reactivity.…”
Section: From the Department Of Microbiology University Of Texas Heamentioning
confidence: 99%